2023
DOI: 10.1007/s40544-023-0785-z
|View full text |Cite
|
Sign up to set email alerts
|

Approximate contact solutions for non-axisymmetric homogeneous and power-law graded elastic bodies: A practical tool for design engineers and tribologists

Valentin L. Popov,
Qiang Li,
Emanuel Willert

Abstract: In two recent papers, approximate solutions for compact non-axisymmetric contact problems of homogeneous and power-law graded elastic bodies have been suggested, which provide explicit analytical relations for the force–approach relation, the size and the shape of the contact area, as well as for the pressure distribution therein. These solutions were derived for profiles, which only slightly deviate from the axisymmetric shape. In the present paper, they undergo an extensive testing and validation by comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In the homogeneous case, we have d* = 1, and therefore, of course, the respective known results [25] are recovered.…”
Section: Power-law Indentersmentioning
confidence: 81%
See 1 more Smart Citation
“…In the homogeneous case, we have d* = 1, and therefore, of course, the respective known results [25] are recovered.…”
Section: Power-law Indentersmentioning
confidence: 81%
“…Recently, Popov [24] published an approximate analytical solution for the slightly non-axisymmetric version of this contact problem, which has proven (by comparison with rigorous numerical solutions) to give very satisfactory results. In the follow-up publication [25], the authors thoroughly tested the quality of the suggested approximate analytical solution for contact geometries that are far from axial symmetry and found that it is even well-applicable to indenters with random three-dimensional shapes, e.g., a single asperity of a rough surface.…”
Section: Introductionmentioning
confidence: 99%